Characteristics and outcome of congenital mesoblastic nephroma: A report of 376 patients registered in the SIOP 93-01, SIOP WT 2001, UK-IMPORT, and AIEOP protocols - Paola Quarello; Rana Dandis; Tanzina Chowdhury; Arnauld Verschuur; Jesper Brok; Gordan Vujanic; Christian Vokuhl; Paola Collini; Aurore Coulomb; Annalisa Serra; Davide Biasoni; Paula Flores; et al. (PLoS ONE, 2026)
Background Congenital mesoblastic nephroma (CMN) is the most common renal neoplasm diagnosed in the very first months of life. Complete nephrectomy only is the gold standard treatment. Objectives and methods This retrospective study aimed to explore the characteristics and outcome of CMN patients registered in the SIOP 93–01, SIOP WT 2001, UK-IMPORT, and AIEOP studies (1993–2019). Results A total of 376 CMN cases were identified, with a median age at diagnosis of 28 days. Stage information was available for 337 patients: 92/337 (27.4%) were diagnosed with stage I, 177/337 (52.6%) with stage II, and 67/337 (20%) with stage III. Among 272 patients with available histological data, 113/272 (41.5%) had classic, 105/272 (38.6%) cellular, and 54/272 (19.9%) mixed subtype. Treatment details were available for 314 patients; 248 (79%) underwent initial surgery, and 66 (21%) received preoperative chemotherapy. Among the latter group, 60% of patients showed a measurable reduction in tumor volume, indicating a favorable response to chemotherapy. The 5-year event-free survival rate was 93.8%, and the overall survival rate was 96.9%. The cumulative 5-year incidence of relapse was 5.3%, with a median time to recurrence of 4 months. Of the 16 relapse cases, 8 were in the cellular subtype, 5 in the mixed subtype, and 3 in the classical subtype. Conclusions This study confirms that CMN patients have an excellent outcome, with complete surgical resection being curative in the majority of cases. Chemosensitivity is observed in a significant proportion, suggesting that neoadjuvant chemotherapy may be a viable option in selected cases. While age at diagnosis, histological subtype, and survival outcomes are consistent with previous reports, we highlight that recurrences, though infrequent, tend to occur early and are not restricted to the cellular subtype. Further prospective studies and molecular investigations are required to refine clinical management strategies and update treatment recommendations.